2017
DOI: 10.1049/iet-bmt.2017.0049
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Bayesian decision theory‐based secure multimodal fusion framework for soft biometric traits

Abstract: In a soft biometric-based model, multiple soft biometric characteristics are fused with one or more primary biometric traits in a multimodal environment. In this study, the authors have reviewed a Bayesian decision theory-based fusion technique and considerably improved its performance by first identifying some of its limitations and subsequently modifying it accordingly. Specifically speaking, they have utilised the notion of Gaussian functions and a novel dynamic soft biometric weight assignment (DSWA) schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…To validate the performance of our method, we compare our proposed hybrid fusion scheme with other recent methodologies in literature. Besides hybrid fusion methods [12,37], we include few other recent state-of-the-art fusion approaches based on score level [25,18,15,22,9] and decision level fusion [31,17]. As described in performance evaluation, it can be observed that the proposed method performs optimally than the other approaches with respect to EER (see Figure 4 -6).…”
Section: Statistical Evaluation Of Proposed Hybrid Fusion Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To validate the performance of our method, we compare our proposed hybrid fusion scheme with other recent methodologies in literature. Besides hybrid fusion methods [12,37], we include few other recent state-of-the-art fusion approaches based on score level [25,18,15,22,9] and decision level fusion [31,17]. As described in performance evaluation, it can be observed that the proposed method performs optimally than the other approaches with respect to EER (see Figure 4 -6).…”
Section: Statistical Evaluation Of Proposed Hybrid Fusion Methodsmentioning
confidence: 99%
“…In case of Virtual A database, the technique proposed in [12] performs better than the proposed method, but it involves complex evaluation for global error optimization using PSO. The decision fusion methods involve AND rule and OR rule-based fusion proposed by Kelkboom et al [17] and Bayesian classifier fusion proposed by Sadhya et al [31]. Table 3 reports the EER and GMR @ 0.01% FMR, obtained using the proposed and existing weighting techniques.…”
Section: Statistical Evaluation Of Proposed Hybrid Fusion Methodsmentioning
confidence: 99%
See 3 more Smart Citations